2012
DOI: 10.1111/j.1468-1331.2011.03652.x
|View full text |Cite
|
Sign up to set email alerts
|

Low ankle–brachial index is a predictive factor for initial severity of acute ischaemic stroke

Abstract: Patients with low ABI values presented with more severe ischaemic stroke. Contribution of pre-existing PAD to leg weakness may play a role in the initial severity of stroke in patients with PAD. Our findings suggest that poor clinical outcomes in patients with PAD may be partially explained by their increased likelihood for severe stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
6
21
1
Order By: Relevance
“…According to several studies, older age, lower BMI, diabetes mellitus, atrial fibrillation and the NIHSS score at admission are significantly associated with PAD among Asian patients with AIS, which is consistent with the present results . Subclinical or clinical leg dysfunction with PAD might play a role in the initial stroke severity estimated using the NIHSS score in patients with a low ABI .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to several studies, older age, lower BMI, diabetes mellitus, atrial fibrillation and the NIHSS score at admission are significantly associated with PAD among Asian patients with AIS, which is consistent with the present results . Subclinical or clinical leg dysfunction with PAD might play a role in the initial stroke severity estimated using the NIHSS score in patients with a low ABI .…”
Section: Discussionsupporting
confidence: 91%
“…However, the prevalence of low ABI values (24.2%) in the present study was relatively higher than that previously reported in patients of Asian ethnicity regardless of the effect of atrial fibrillation. In general, Asian patients have a lower prevalence of low ABI values (7–18%) than white patients (20–30%) . The main explanation for the differences in the prevalence of PAD among patients with AIS between the present study and other Asian studies might be the age of the patients.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Low ABI is commonly defined as ABI <0.9 and provides good sensitivity (80%) and excellent specificity (95%) to detect PAD [4]. ABI is also associated with poor initial stroke severity [21] and predicts poor prognosis and mortality in patients with stroke [2]. However, several previous studies have shown that low ABI was not sensitive enough to detect asymptomatic PAD in the general population [22].…”
Section: Discussionmentioning
confidence: 99%